Application of an insecticidal bait to control adults of tecia solanivora (povolny) (lepidoptera: gelechiidae) in potato (2001)
In order to measure the effect of the application of aninsecticide bait with the help of a sugary substance to controladults of Tecia solanivora (Povolny) (Lepidoptera:Gelechiidae), tests were carried out in laboratory and undergreenhouse, at the Agronomy School at the NationalUniversity of Colombia, in Bogotá. A breeding was managedin the Laboratory of Entomology to obtain the entomologymaterial for the different tests. Four attractants wereevaluated: Sugar, molasses, honey and panela (a kind of brown sugar). Honey resulted as the most attractive substance. Three insecticides (with and without honey) as a bait were tested in the laboratory trial: Beta-cyfluthrin EC 0,25; Chlorpyrifos-Betacyfluthrin EC 450 and Chlorpyrifos-Betacyfluthrin EC 262,5, with two doses each: 0,5 cmvl, and1,0 cml/l.; with the best two insecticides (Chlorpyrifos-Betacyfluthrin EC 450 and Chlorpyrifos-Betacyfluthrin EC262,5) we did a greenhouse trial, caging four plants ofpotato,variety "parda pastusa", and placing 20 adults of T.solanivora (10 females and 10 males) inside each cage. Twomethods were used to apply the treatments: a spray to theinferior third of one of the four plants and a recipient trapcontaining the insecticide bait. The design was a completelyrandomized block (RCB) with four replications. The variablesevaluated were per cent mortality to calculate percenteffectiveness with the Schneider-Orelli method, per centincidence ofthe tubers and per cent infestation ofthe tubers.In the greenhouse experiment Chlorpyrifos-Betacyfluthrin EC450 (1 ,Ocm3/L) with honey gave the highest per cent mortality (72,5%), the highest per cent effectiveness (69,4%) and the lowest percentage of tuber infestation (11,3%). There was no significant difference between the spraying methods and the recipient trap to apply the insecticidal bait.